Regional innovator networks: A review and an application with R - Holger Graf (Friedrich Schiller University Jena, 2017)
The article serves as an introduction to the empirical analysis of innovation or knowledge networks based on patent data with a particular focus on regional networks. I provide a review of the literature of innovation networks and how it connects to systemic approaches within the field of innovation studies. The SNA methodology is introduced by performing a comparative regional network study based on the publicly available OECD patent databases.
Keywords: L14; O31; R11; 330; Regional Innovation; Network Analysis; Patent Data